Novel and established biomarkers to complement risk scores in patients with acute decompensated heart failure – a pilot study - Valentin Hähnel; Victoria Meretz; Christian Butter; Vera Paar; Christoph Edlinger; Michael Lichtenauer; Ronald Biemann; Berend Isermann; Meike Hoffmeister; Michael Haase; Anja Haase-Fielitz; Marwin Bannehr (American Heart Journal Plus)
Study Objective: There are several risk scores for mortality in patients with acute decompensated heart failure (ADHF) such as the European Collaboration on Acute Decompensated Heart Failure Score (ELAN-HF Score), the ADHF/NT-proBNP-Score or A2B-Score (age, anemia, BNP). The aim of this study was to evaluate the predictive value of such risk scores with and without addition of novel cardiorenal biomarkers. Design & Setting: Single-center, exploratory prospective cohort study at the University Hospital Heart Centre Brandenburg. Participants: Forty-four adult patients hospitalized for ADHF. Interventions: Measurement of established and novel biomarkers at hospital admission including N-terminal-pro brain natriuretic peptide (NT-pro-BNP), troponin T, creatinine, cystatin C, soluble suppression of tumorigenicity 2 (sST2), Neprilysin, Dickkopf-3 (DKK3), interleukin-6 (IL-6), growth differentiation factor-15 (GDF-15), Galectin-3, Progranulin and urine neutrophil gelatinase-associated lipocalin (uNGAL). Main Outcome Measures: Analysis of predictive indices of ELAN-HF, ADHF/NT-proBNP and A2B-Scores for 90-day mortality with and without adding biomarkers. AUC <0.8 was considered as fair, ≥0.8 as good and > 0.9 as excellent predictive value. Results: Median age was 78.0 (25th–75th percentiles 69.3–83.8) years, 50 % (22/44) were female. Twelve patients (27.3 %) died within 90 days after discharge. All three risk scores were higher in non-survivors and showed fair AUC for 90-day mortality (ELAN-HF: 0.792 [0.639–0.901], p = 0.003; ADHF-NT-proBNP score: 0.749 [0.559–0.938], p = 0.012; A2B score: 0.734 [0.541–0.927], p = 0.017). Adding troponin T, cystatin C-based estimated glomerular filtration rate (eGFR) or uNGAL to risk scores was associated with an area under the curve (AUC) >0.80 for all models. Combination of troponin T, cystatin C-based eGFR and uNGAL increased risk scores to AUC >0.91. Conclusion: These findings imply that further evaluation of the addition of a panel of cardiorenal biomarkers to ADHF risk scores is warranted.